Genes, circuits, and precision therapies for autism and related neurodevelopmental disorders - Sahin, Mustafa; Sur, Mriganka (Science (American Association for the Advancement of Science), 2015)
When the brain does not develop normally, the disabilities that ensue can affect a person for life. Sahin and Sur review how emerging knowledge of the molecular biology behind a suite of neurodevelopmental disorders is shedding light on the group as a whole. The new knowledge offers tantalizing leads toward more effective therapies. Science , this issue p. 10.1126/science.aab3897 Research in the genetics of neurodevelopmental disorders such as autism suggests that several hundred genes are likely risk factors for these disorders. This heterogeneity presents a challenge and an opportunity at the same time. Although the exact identity of many of the genes remains to be discovered, genes identified to date encode proteins that play roles in certain conserved pathways: protein synthesis, transcriptional and epigenetic regulation, and synaptic signaling. The next generation of research in neurodevelopmental disorders must address the neural circuitry underlying the behavioral symptoms and comorbidities, the cell types playing critical roles in these circuits, and common intercellular signaling pathways that link diverse genes. Results from clinical trials have been mixed so far. Only when we can leverage the heterogeneity of neurodevelopmental disorders into precision medicine will the mechanism-based therapeutics for these disorders start to unlock success.